«A grant navie outre la mer» (v.2256): the naval battle of Wistasse the monk (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2020)
Wistasse le Moine – a 13th century French novel - is a tale, halfway between real history and literary invention, of a real-life character, Eustache Busket, lord of some lands in the Boulogne-sur-Mer region, on the English Channel. The story of his adventures in struggle against the Count of Boulogne Renaud de Dammartin, who robbed him of his fiefdom, is mixed with real events, which saw the kingdoms of France and England fighting. The fight is full of twists and turns, until the novel relates some true historical facts, which culminate in the Battle of Sandwich (1217), where the British win the French, and Wistasse-Eustache, who is the leader of the French fleet, is defeated and dies.
Keywords: Wistasse le Moine; Battle of Sandwich; First Baron War; English Medieval History; outlaws in medieval literature